Operative cardiac surgery - Spray, Thomas L.; Acker, Michael A. (Michael Andrew) (Boca Raton, FL : CRC Press, 2019)
The sixth edition of this acclaimed and established operative atlas continues to provide a unique level of comprehensive detail on operative surgery of the heart and great vessels. With an international list of authors, the chapters have been updated and complemented by the same high quality artwork that has established this operative guide as the gold standard reference for the cardiac surgeon. This new edition retains the format of initial principles and justification for the procedure, followed by preoperative investigations and preparation, the operative procedure, and postoperative management. New chapters have been added on the latest techniques such as minimal invasive surgery, robotic surgery and off-pump bypass surgery. The chapters are arranged in seven sections, with each section emphasising the overall management of patients, tricks of the trade of individual authors and discussion of technical and clinical judgement. With this new and updated edition, Operative Cardiac Surgery remains the pre-eminent operative guide to a full range of cardiac conditions. Video clips of cardiac procedures, both common and rare, are included within the VitalSource edition.
Section One Perioperative Management. Echocardiography for Cardiac Surgery. Cardiopulmonary Bypass: Access, Technical Options and Pathophysiology. Circulatory Arrest: Retrograde vs Antegrade Cerebral Protection. Intraoperative Myocardial Protection. Section Two Surgery for Ischemic Heart Disease. On Pump Coronary Artery Bypass Grafting. Off-pump coronary artery bypass grafting. Expanded use of Arterial Conduits. Reoperative Coronary Artery Bypass Grafting. Repair of Postinfarction Ventricular Septal Defect. Robotic total endoscopic coronary artery bypass grafting (TECAB) Section Three Surgery for Valvular Heart Disease. Aortic valve replacement. Minimal Access Aortic Valve Surgery. TAVR: Transfemoral and Alternative Approaches. Aortic Valve Repair. Mitral Valve Replacement. Mitral Valve Repair. Minimal access Mitral Valve Surgery. Robot-Assisted Mitral Valve Surgery. Tricuspid Valve Surgery. The Pulmonary Autograft for Aortic Valve Replacement. Valvular Endocarditis. Valve Sparing Aortic Root Replacement. Section Four Surgery for Heart Failure.Heart Transplantation. Heart- Lung Transplantation. Lung Transplantation. Permanent continuous flow left ventricular assist devices. Temporary Mechanical Assistance (ECMO). Left Ventricular Reconstruction. Surgery for Hypertrophic Cardiomyopathy. Standard Surgical Therapies for CHF/MVR for Heart Failure. Section Five Thoracic Aortic Disease. Ascending Aortic Aneurysm. Hybrid aortic arch repair. Thoracoabdominal aortic aneurysms. Thoracic Endovascular Aortic Repair. Aortic Dissection: Type A and B. Section Six Surgery for Cardiac Rhythm Disorders & Tumors. The Cut-and-Sew Maze-III Procedure for the Treatment of Atrial Fibrillation. Cardiac Tumors. Pacers and BV Pacers. Section Seven Surgery for Congenital Heart Disease. The Anatomy of Congenital Cardiac Malformations. Palliative procedures: Shunts and pulmonary artery banding. Total anomalous pulmonary venous connection and cortriatriatum. Atrial septal defect. Atrioventricular septal defect. Bidirectional Glenn and hemi-Fontan procedures. Fontan procedure for functionally single ventricle and double-inlet ventricle. Double-outlet ventricles. Ebstein's anomaly. Ventricular septal defect. Tetralogy of Fallot. Pulmonary atresia with ventricular septal defect. Right ventricular outflow tract obstruction with intact ventricular septum. Left ventricular outflow tract obstruction. Transposition of the great arteries with left ventricular outflow tract obstruction. Transposition of the great arteries with right ventricular outflow tract obstruction. Anatomical repair of transposition of the great arteries. Congenitally Corrected Transposition. Persistent truncus arteriosus. Persistent Ductus Arteriosus. Aortopulmonary Window. Coarctation of the aorta: Repair of coarctation and arch interruption. Congenital anomalies of the aortic arch. Hypoplastic left heart syndrome. Coronary anomalies. Cardiac transplantation for congenital heart disease. Lung and heart-lung transplantation for congenital heart disease. Ventricular assist devices for congenital heart disease. Congenital Mitral valve repair. Aortic valve repair.Index
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Heart -- Surgery; MEDICAL / Surgery / Thoracic; MEDICAL / Surgery / General